The process of testicular regression also impacts the physiology of the epididymis of the bat Molossus molossus, although with a delay in epididymal response due to sperm storage - Soares, Emília M. (2021)
Responsible for post-testicular maturation, concentration, protection and sperm storage, the epididymis is an organ that can be easily subdivided into three segments: caput, corpus and cauda. Each epididymal region displays different morphology and functions within the sperm maturation process. Despite the great importance of this organ, studies on its morphology and hormonal control in bats remain scarce. Thus, the aim of this study was to morphologically analyze the epididymis of the bat Molossus molossus (Chiroptera: Molossidae), in order to evaluate its morphological and morphometric variations, as well as some aspects of its hormonal control during the annual reproductive cycle. For this purpose, 60 sexually adult males were used in this study, comprising five specimens collected monthly for one year to form 12 sample groups. The epididymis was subjected to morphological, morphometric and immunohistochemical analyses. The results demonstrated that the processes of total testicular regression and posterior recrudescence suffered by M. molossus also impacts the physiology of the epididymis, however, a delay in the epididymal response is seen due to the storage of sperm. Similar to other mammals, the epididymis of M. molossus has a large predominance of principal and basal cells. The epididymal seasonal variations appear to be directly correlated to rainfall and photoperiod, but not to temperature. Meanwhile, epididymal physiology appears to be regulated, at least partially, by the expression of the androgen receptor in epithelial cells, which has agonist effects on cell proliferation.